PERAN KEPALA MADRASAH IBTIDAIYAH MUHAMMADIYAH DALAM MEMBENTUK KEUNGGULAN MENUJU MADRASAH UNGGULAN MAGELANG - Ahwy Oktradiksa; Irham Nugroho (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
There are madrassas which indicates a superior madrassa madrassa in fact superior to those faced with the efficiency and effectiveness of management is still found many obstacles to realize as a madrasah that really excels. The research focused on the study of the role of headmaster in the form of superior madrassa. The formulation of the problem in general is "How far the efficiency and effectiveness of the headmaster in the form of superior madrassa in Magelang?". Operationally, these problems are detailed in the following research questions: How can the effectiveness and efficiency of the planning role of the headmaster to form Madrasah excellence in the City and District of Magelang ?, How strategic components that characterize featured madrasa in the city and district of Magelang managed ?. The general objective of this study is to examine in depth and analyze the efficiency and effectiveness of superior madrassa in the District and the City of Magelang. The method used in this research is quantitative research methods. As for the data collection is done through questionnaires, interviews, observation, and documentation study. Based on the results of the study concluded that the madrasa excel in the District and City of Magelang yet overall managing madrasah efficiently and effectively in accordance with the criteria of efficiency and effectiveness in the management of superior madrassa. The condition occurs as a result of the planning, implementation, development and quality assurance, monitoring and control, as well as the Review and evaluation of the strategic components of madrasas have not managed efficiently and effectively.Key Word : Kepala MI, Madrasah Unggulan